Moulie Vidas. Tradition and the formation of the Talmud. Princeton, N. J.: Princeton University Press, 2014. 239 p.; 23 cm. ISBN 978-0-691-17086-2 (en rústica); ISBN 978-0-691-15486-2 (en cartoné). - Ferrer, Joan (TAMID. Revista Catalana Anual d’Estudis Hebraics, 2017)